Svalbox-DOM_2023-0022 - Betlem, Peter; Rodes, Nil; Hartz, William; Svalbox team (Zenodo, 2023)
Model description: Digital outcrop model of Peak 1086, in western Elnabreen, Andrée Land, Svalbard archipelago. Data availability: All uploaded archives are to be extracted to the same directory for a functional working environment, i.e., at the very least consisting of a project folder with the data and metashape subdirectories. The included processing report specifies the processing parameters that were used as input for the processing software (Agisoft Metashape, v2.0.2.16334). Georeferencing data use CRS epsg:4326.Exported model data use CRS epsg:32633. Show and visualise on Svalbox.no : Through Svalbox we aim to take geoscientific research and education to the next level – with the simple motto of placing all key information and data sets in their correct spatial position. We bring modern technology, in particular cost-effective digital outcrops, to complement more than 200 years of geoscientific research on Svalbard. Finally, Svalbox provides a sustainable platform for sharing results, workflows and teaching material with the wider geoscientific community. For more information, contact the Svalbox team at svalbox[at]gmail.com. This data set forms part of the Svalbox Digital Model Database. Please cite the database alongside this resource: Betlem, Peter and Rodes, Nil and Birchall, Thomas and Dahlin, Anders and Smyrak-Sikora, Aleksandra and Senger, Kim. (2023). The Svalbox Digital Model Database: A Geoscientific Window into the High Arctic. Geosphere. https://doi.org/10.1130/GES02606.1